2009
DOI: 10.1590/s1517-83822009000100021
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance profile of Enterococcus spp isolated from food in Southern Brazil

Abstract: Fifty-six Enterococcus spp. strains were isolated from foods in Southern Brazil, confirmed by PCR and classified as Enterococcus faecalis (27), Enterococcus faecium (23) and Enterococcus spp (6). Antimicrobial susceptibility tests showed resistance phenotypes to a range of antibiotics widely administrated in humans such as gentamycin, streptomycin, ampicillin and vancomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 16 publications
2
29
2
13
Order By: Relevance
“…Also, Riboldi et al (2009) isolated Enterococcus spp. from foods in Southern Brazil and detected only one vancomycin resistant Enteroccoccus faecalis isolated from colonial cheese.…”
Section: Antibiotic Resistance Of Enterococci Strainsmentioning
confidence: 99%
“…Also, Riboldi et al (2009) isolated Enterococcus spp. from foods in Southern Brazil and detected only one vancomycin resistant Enteroccoccus faecalis isolated from colonial cheese.…”
Section: Antibiotic Resistance Of Enterococci Strainsmentioning
confidence: 99%
“…Dissemination of VRE and other resistant enterococci may be either by infected patients or by the transfer of bacteria from contaminated medical instruments and surfaces (5). Nevertheless, several studies showed the presence of VRE in farm animals (4,6,7) and animal-originated food samples in different countries (1,(14)(15)(16), suggesting that the food chain would be a potential vehicle for transmission of VRE from animals to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Este resultado foi similar aos observados por Fracalanzza et al (2007) faecalis, E. faecium e Lactobacillus reuteri no trato digestivo de camundongos e transferido entre cepas de L. curvatus em salsichas fermentadas, corroborando com a hipótese de que Enterococcus resistentes podem contaminar os alimentos, entrar no trato gastrointestinal humano e colonizar os seres humanos e/ou passar seus genes de resistência para bactérias comensais presentes no trato intestinal humano, situação de risco para a saúde pública (Riboldi et al 2009). …”
Section: Resultados E Discussão Isolamento Microbiológico Em Amostrasunclassified
“…compõem a microbiota intestinal de seres humanos e animais saudáveis e estão amplamente distribuídos no ambiente (Biavasco et al 2007, Casal et al 2009, López et al 2009, Riboldi et al 2009). As duas espécies mais importantes, E. faecium e E. faecalis, estão frequentemente implicadas em infecções em animais e humanos imunocomprometidos, como bacteremia, septicemia, infecções do trato urinário, infecções de feridas, meningites e endocardites (Cauwerts et al 2007, Gama 2008, Kense et al 2011, Zou et al 2011.…”
Section: Introductionunclassified